The demic expansion of Yangshao culture inferred from ancient human genomes - Lei Sun; Hao Ma; Rui Wang; Zhijiang Wu; Limin Qiu; Haodong Chen; Chuan-Chao Wang (BMC Biology)
Abstract Background Originating from the middle Yellow River, Yangshao culture is one of the most influential archaeological cultures in Neolithic China. It has long been debated whether there was a genetic substructure between the core Yangshao sites and those representing regional variants of the Yangshao culture, such as the Qinwangzhai culture. The excavated human remains from the burials at the Zhanmatun site, which belonged to the Qinwangzhai culture, present ideal material for inferring the population dynamics accompanying the cultural expansion. Results In this study, we analyzed genome-wide data from 12 human remains obtained from the Zhanmatun site. The results indicated that Zhanmatun individuals were genetically homogeneous with all published Yangshao culture-related individuals from the core region of Yangshao and its periphery as well as Late Dawenkou culture-related Xixiahou people in the east, with no tracts of genetic influence from Neolithic Southern East Asian in the south. Conclusions Our findings support a demic diffusion model for Yangshao culture expansion, where human migration, rather than mere cultural diffusion, played a dominant role in spreading Yangshao-related ancestry across northern China.